STUDIES OF THE BIOLOGICAL AND THERAPEUTIC EFFECTS OF ARGENTINE STINGLESS BEE PROPOLIS - Brodkiewicz, Yanina; Marcinkevicius, Karenina; Reynoso, Marcos; Salomon, Virginia; Maldonado, Luis; Vera, Nancy (Journal of Drug Delivery and Therapeutics, 2018)
Meliponids are native bees of the Americas, characterized by having no sting (ANSA). Some live in the Yunga forests of northern Argentina, a place rich in a diversity of this type of bees of which at least thirty-three species may be found. Propolis is a resinous substance that bees collect from plants exudates. Chemical composition and functional properties vary according to the flora of the place where the hives are. They have been valued by humans for their biological properties for centuries. This study is aimed at investigating the antinociceptive, antioxidant and anti-biofilm activities of propolis from the stingless bees Tetragonisca fiebrigi Schwarz and Scaptotrigona jujuyensis Schrottky found in Estación Experimental Agropecuaria Famaillá of INTA, Tucumán, Argentina. Analgesic activity of the extracts was estimated against acetic acid induced writhing, tail immersion method and formalin test. Antioxidant capacity was evaluated using DPPH free radical scavenging and β-carotene bleaching assays. Propolis anti biofilm activity was tested on Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATTC 6538P bacteria. Phytochemical constituents were obtained using standard chemical methods. The propolis alcoholic extracts of the studied species possess antinociceptive activity at both central and peripheral levels as demonstrated by the three algesia tests used. Both propolis extracts were effective antioxidants in DPPH and β-carotene linoleic acid model systems. S. jujuyensis propolis tested at all doses against S. aureus and P. aeruginosa presented a selective biofilm inhibition unrelated to bacterial growth inhibition, thus achieving a reduction in pathogenicity. The chemical studies revealed the presence of sterols, triterpenes, catechins, coumarins, flavonoids, phenols, tannins and anthocyanidins. Chemical composition observed in the T.fiebrigi and S. jujuyensis propolis, suggest that those responsible for the activity would be chemical compounds of a non-phenolic nature. Our data indicate that geopropolis is a natural source of bioactive substances with promising beneficial properties for human health. Isolation and identification of compounds responsible for the pharmacological activities displayed by propolis has started.